2016
DOI: 10.4314/gjss.v14i1.3
|View full text |Cite
|
Sign up to set email alerts
|

“Climate change and recent severe flooding in Uyo, Akwa Ibom State, Nigeria”

Abstract: This paper considered the phenomenon of climate change in relation to frequent and intensified flood problems in Uyo, the Capital City of Akwa Ibom State, Nigeria. Empirical evidence on the onset of climate change in Nigeria was presented. Flood problems worldwide were highlighted, together with their impacts in terms of deaths, economic losses and associated human sufferings. To this end, a detailed rainfall analysis was conducted for the study area, Uyo, using statistical distributions commonly deployed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…They equally suggested proper channelization of Calabar urban drainage system, stringent flood control legislation, and development control measures that will play positive roles in mitigating the challenges of flooding. Ekpoh (2015) assessed climate change and recent severe flooding in Uyo, Akwa Ibom State. He designed a detailed rainfall analysis for Uyo using statistical distributions commonly deployed to describe climate states, such as the mean, the running mean, the standard deviation, coefficient of variability, skewness, and kurtosis.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They equally suggested proper channelization of Calabar urban drainage system, stringent flood control legislation, and development control measures that will play positive roles in mitigating the challenges of flooding. Ekpoh (2015) assessed climate change and recent severe flooding in Uyo, Akwa Ibom State. He designed a detailed rainfall analysis for Uyo using statistical distributions commonly deployed to describe climate states, such as the mean, the running mean, the standard deviation, coefficient of variability, skewness, and kurtosis.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Basically, in recent decades, flooding has led to the loss of thousands of lives and properties. According to available studies, flooding in Nigeria is caused by weak implementation of planning policies, streams and channel obstruction due to indiscriminate waste disposal habits and human activities in flood plains (Ituenet al, 2014;Ekpoh, 2015;Udoh, 2015 andEvan et al, 2017;Abraham et al, 2021). Specifically, flooding has affected the lives, properties and sustainability of the environment as noted in available studies.…”
Section: Introductionmentioning
confidence: 99%
“…From a pre-industrial level of 280 parts per million by volume (ppmv), carbon dioxide, for instance, increased to 380 ppmv by 2005; an increase of about 40 per cent. The projection for 2015 level of carbon dioxide in the atmosphere was put at 400 ppmv [5]. It should be stated here that the preponderance of greenhouse gases in the earth's atmosphere is responsible for the formation of a gas layer in the troposphere called the greenhouse gas layer.…”
Section: Global Warmingmentioning
confidence: 99%
“…Therefore, the focus of this section is on scientific studies with empirical evidence. Studies have shown that Nigeria is already in the thick of climate change [5,7,8,9,10,11,12]. In a study that involved 30 meteorological stations and 105 years of observation, [13] carried out long-term temperature analysis and the result showed that the mean temperature for Nigeria since 1901 remained steady until the late 1960s when it started a gradual rise that has continued to the present time, in response to global warming.…”
Section: Empirical Evidence Of Climate Change In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation